A study of the impact of masstige strategies on brand coolness and brand happiness - Sauter, V.; Bilro, R. G.; Loureiro, S. M. C. (16th Annual Conference of the EuroMed Academy of Business. Business Transformation in Uncertain Global Environments, 2023)
Luxury was once exclusive and limited to a small group of wealthy individuals, but as purchasing power increased, traditional luxury brands began to lose their exclusivity. Brands realized they needed to expand their target audience to sustain their growth, leading to the birth of the masstige phenomenon, where premium but attainable products are marketed to the masses. While the masstige strategy has been proven effective, it has been largely ignored and underestimated in the literature. Moreover, the concept of brand coolness and its impact on customers is still in its nascent stage and will also be examined, particularly in the context of mobile brands, which have become a high priority for individuals in their everyday lives. So, this paper aims to contribute to the branding literature by examining the relationship between brand coolness and masstige, investigating how customers relate to their mobile brands in terms of different branding components and constructs, such as masstige, brand coolness, and brand happiness.